Commencement, Salisbury University, Spring 1997 - (:unkn) unknown (My University, 1997)
Commencement ceremonies at have been held for graduates at Salisbury University since 1926, sometimes after each semester but typically in the spring. Programs always list the names of graduates and occasionally list hometown, degree, or major.
Keywords: Salisbury (Md.); Salisbury State University; Commencement ceremonies